BMI changes and its effects on a paediatric obese population in the COVID-19 pandemic - Azevedo, Inês Alexandra (2022)
Introduction: The COVID-19 pandemic represented a major threat to global health. The special circumstances and changes to everyday life due to the worldwide measures had a strong impact, particularly in childhood and adolescent obesity. We aimed to evaluate the impact on the treatment of obesity and on the expression of comorbidities during the first lockdown. Methods: Retrospective cohort study of overweight and obese children/adolescents (6-18 years), followed at reference outpatient clinic, since 2018. Anthropometric and biochemical parameters were evaluated. Results: We studied 71 children/adolescents (52.1% female) with a median age of 10 years. 87.3 % were obese and a family history of obesity was positive in 51.4%. After home confinement, a significant increase was observed regarding body mass index (p<0.001) and there was worsening of insulin levels (p<0.001), homeostasis model assessment for insulin resistance (p=0.005), and aspartate aminotransferase (p<0.001), but not reaching pathologic levels. Therefore, there was no significant worsening of comorbidities after the lockdown. Conclusion: During the COVID-19 pandemic, there was a worsening in the magnitude of obesity. However, there was no significant repercussions on its comorbidity, which does not allow to exclude any long-term consequences.